Escape to California - Greenhut, Josh; Brown, Jeff, 1926-2003 (Flat Stanley's worldwide adventures, 2014)
While on vacation in San Francisco, Stanley meets a girl who enlists his help in performing a trick: escaping from Alcatraz.